Leaching of nickel laterite with a solution of ammonia and ammonium carbonate utilizing solids liquid separation under pressure - Erasmus, Mothobi (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: Leaching of nickel laterite was conducted with a solution of ammonia and ammonium carbonate in a closed vessel. The vessel used in this study was designed to leach and perform solid-liquid separation at the same time. For solid-liquid separation, stainless steel sintered metal filter media were used. The sintered metal filter medium was selected for its high strength to withstand pressure, chemical resistance to caustic solution and back flushing properties. Optimum leaching conditions were determined by varying temperature, ammonia concentration, ammonium carbonate concentration and oxygen pressure. After leaching and filtration, the pH of the leach liquor was measured and samples were analyzed for dissolved metals (Ni, Fe and Co) using atomic absorption spectrophotometry. The most significant variable effect on leaching of nickel was the ammonia concentration. The maximum dissolution of nickel from the unroasted ore was 11.90% at 4 M NH3, 100oC, 2 M (NH4)2CO3 and 2 bar O2 pressure. Optimization from the leaching data was done using response profiling and desirability in Statistica software. Optimum leaching conditions were determined to be 3 M NH3, 2 M (NH4)2CO2, 100oC and 2 bar O2 pressure. The mineralogy of the ore before and after leaching was studied to understand why nickel extraction from unroasted ore was poor. XRF analysis of solids after leaching showed that iron, silicon, and magnesium remained the same. The only metal which showed significant decrease from solids was nickel. XRD analysis of solids after and before leaching showed that most mineral phases present in the ore are not affected by the leaching solution. SEM with EDS detection was used to determine nickel distribution within the ore. The results showed that nickel is mostly associated with iron. The iron is surrounded by magnesium and silicon. Silicate minerals do not react with ammonia and ammonium carbonate solution. From filtration experiments, the filtration differential pressure had no significant effect on the filtration rate. An average filtration rate of 0.29±0.07 ml/min.cm2 was obtained. The filtration rate from these experiments was very low. The main reason was due to quick pore clogging of sintered metals. Pore clogging was found to be mainly on the surface of the filter medium. Laterites have been found to have low permeability due a lot of clay present in the ore. Rheological studies on this ore showed that the ore has shear thickening behavior. However, a very clear filtrate was obtained. After each leach and filtration experiment, the sintered metals was unblocked by back flushing with water and air. Back flushing was successful because all 18 experiments were carried out using the same sintered filter medium. The effect of roasting the ore prior to leaching was investigated using optimum conditions obtained when leaching the unroasted ore. There was a slight improvement in nickel extraction when the ore was roasted. The average percentage extraction of nickel from 3 experimental runs was 19.25%±0.19 at 100oC, 3M NH3, 2M (NH4)2CO3, and 5 bar oxygen pressure. Some part of nickel in the ore was unextractable due to association of nickel with recrystallized silicate minerals in the reduced ore. Roasting improved permeability of the ore. The filtration rate improved significantly after roasting the ore. The average filtration rate was 2.60±0.05 ml/min.cm2. Dissolution kinetics of the unroasted and roasted saprolitic laterite were investigated with regard to the effects of temperature, ammonia concentration, ammonium carbonate concentration, and oxygen pressure. For the unroasted ore, it was found that dissolution rate and degree of nickel extraction increases with increasing temperature. Increase in ammonia concentration improves the degree of nickel extraction. Nevertheless, nickel extraction does not depend entirely on ammonia concentration because even when ammonia concentration is high and ammonium carbonate concentration is zero nickel extraction is low. An increase in ammonium carbonate concentration also increases the degree of nickel extraction. Ammonium carbonate is critical for the extraction, since ammonium ions in the solution prevent hydrolysis of the nickel ammine complex. Oxygen did not have a significant effect on the degree of nickel extraction. The leaching of nickel laterite was found to be a two stage leaching process. In the first stage, the dissolution of nickel is faster but after 15 minutes, the reaction rate is reduced. The reaction rate is reduced by inert minerals which host nickel. These minerals contain iron magnesium and silicon. The fast dissolution of nickel in the first stage represents leaching of free nickel in the ore. The data for the second stage of leaching was analyzed by the shrinking core model, and the results suggested that the dissolution rate is controlled by mixture kinetics (ash layer diffusion and surface reaction control). The activation energy for the dissolution reaction was calculated as 56.5 KJ/mol. The reaction order with respect to ammonia and ammonium carbonate were determined to be 0.3 and 0.26 respectively. For the roasted ore, the highest degree of nickel extraction was obtained at 60oC, 3M NH3, 2M (NH4)2CO3, and 5 bar oxygen pressure. The percentage extraction under these conditions was 28.7%. Temperature did not have a significant effect on the leaching rate. An increase in NH3 and (NH4)2CO3 increased the final extraction of nickel but did not have any effect on leaching rate in the first stage of leaching. In the absence of ammonium carbonate, nickel extraction is almost zero. The experimental data did not give linear fit to the shrinking core models investigated for the unroasted ore. The reason for this could be due to the sampling time interval which was too far apart, or the leaching behavior of roasted nickel is complicated and cannot explained by shrinking core model alone. Leaching experiments demonstrate that for a high degree metal extraction and improved reaction kinetics with ammonia and ammonium carbonate, the solution temperature should be high (>100oC) for the unroasted ore. In order to leach at high temperature with ammonia and ammonium carbonate a closed vessel is required to prevent reagent loses. The reaction kinetics showed that the reaction is controlled mostly by ash layer diffusion; this indicates that a low degree of nickel extraction in the unroasted saprolitic laterite is due to inert minerals (ash layer) which host nickel within the ore. In order to obtain a high degree of nickel extraction, the ore needs to be roasted under reducing conditions. Roasting conditions need to be carefully controlled to ensure high dissolution of nickel. In fact optimum roasting conditions which will give maximum dissolution of nickel, must be determined before working with the bulk of the ore.